Sintesis Biokomposit Serat Sabut Kelapa dan Resin Poliester dengan Alkalisasi KOH Menggunakan Metode Hand Lay-Up - Nisa, Khadijah Sayyidatun; Melyna, Ella; Samida, Muhammad Rizky Mubarak (Universitas Trunojoyo Madura, 2022)
Development of bio-composite materials is growing rapidly, as these materials are light, strength, and have good resistance to corrosion. Moreover, bio-composite is one of many options to utilize agricultural waste. Polyester resin and coconut coir fiber can be utilized as matrix and filler for bio-composites. Alkalization is a method to obtain high quality cellulose from natural materials. The objective of this study is to examine the effect of KOH concentration on tensile strength and hardness of coconut coir fiber and polyester resin composite. The composite was successfully synthesized using hand lay-up method. Tensile strength and hardness tests were conducted to examine the composite’s physical properties, meanwhile Fourier Transform Infrared was employed to examine the material’s functional group. Bio-composite with coconut coir fiber and polyester ratio=40:60 yielded the highest tensile strength of 6.04 MPa. Furthermore, the composites that are synthesized with alkalization using KOH concentration of 5%wt, 10%wt, 15%wt, and no alkalization produced tensile strength 5.29, 6.92, 3.50, and 3.50 MPa respectively. In addition, the composites with KOH concentration of 5%wt, 10%wt, 15%wt, and no alkalization generated hardness 70, 73, 73, and 72 Shore D respectively. It can be concluded that the higher coconut coir fiber ratio, the higher the bio-composite’s tensile strength.